The Backyardigans Pirate Treasure - Justin Spelvin (United Kingdom Simon Spotlight, 2006)
The Backyardigans set off on a pirate adventure! Pablo, Tyrone, Uniqua, and Austin sail the high seas in search of buried treasure. Who will find the treasure first? And who will walk the plank?
Keywords: Read Aloud -- Read Aloud